2018
DOI: 10.2298/jmmb160923010m
|View full text |Cite
|
Sign up to set email alerts
|

Mineral phases in iron ore sinters produced with oak sawdust substitute fuel

Abstract: In this paper, the effect of oak sawdust-a cheap substitute fuel on the quality of sinter in terms of its phase composition is evaluated. The samples of sinters prepared with 5, 9, and 13% equivalent fixed carbon substitution of coke breeze by oak sawdust were analyzed by light microscopy, SEM-EDS and powder XRD analysis. The microstructure of sinters in places with fuel residues consisted of well-integrated secondary mineral phases, confirming good conditions for sintering. The phase analysis has shown a pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Due to lack of thermodynamic data, kirschsteinite was used instead of iron-calcium olivine for the heat reaction calculation. Equation (9) is in agreement with the formation of phases in penetrated areas observed in other studies [46,47]. In both cases, melt penetration was exothermic in character due to the formation of (iron-)calcium silicates.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Due to lack of thermodynamic data, kirschsteinite was used instead of iron-calcium olivine for the heat reaction calculation. Equation (9) is in agreement with the formation of phases in penetrated areas observed in other studies [46,47]. In both cases, melt penetration was exothermic in character due to the formation of (iron-)calcium silicates.…”
supporting
confidence: 89%
“…By blending coarser limestone or dolomite, the useful basicity decreases and more iron-calcium silicates form in the matrix, as presented in the earlier study [47].…”
Section: Some Implications For the Commercial Sinteringmentioning
confidence: 54%
“…PM-F: an iron-rich mixture; PM-A: a high-alumina mixture (PM-A); PM-S: a high-silica mixture. Note that the composition of the PM-S mixture differs slightly from the range presented in the work by Mežibrický and Fröhlichová [25]. Preliminary reactivity testing of the mixtures revealed that no calcium ferrites could be synthesized at low basicity (CaO/SiO 2 ratio by weight).…”
Section: Synthesis Of Sfca Crystalsmentioning
confidence: 77%
“…The compositions of the starting mixtures were chosen so that they corresponded to the chemical compositions of the Ca 2 (Ca,Fe,Mg,Al) 6 (Fe,Si,Al) 6 O 20 type ferrites, which are frequently found in iron ore sinters. Three different mixtures were prepared: (i) an iron-rich mixture (PM-F) [23]; (ii) a high-alumina mixture (PM-A) [24]; and (iii) a high-silica mixture (PM-S) [25]. The respective mixing ratios of the raw materials are given in Table 2.…”
Section: Synthesis Of Sfca Crystalsmentioning
confidence: 99%
“…Figure 1 shows the operation of a blast furnace, idealized from the perspective of the presence of iron oxides. In the real-world process, the amount of iron oxide cannot be accurately determined due to variations in batch quality [24][25][26][27].…”
Section: Fuel Rate Minimization Model 31 Reduction Of Iron Oxidesmentioning
confidence: 99%